THE ROLE OF EMOTIONAL INTELLIGENCE IN EDUCATIONAL LEADERSHIP - Muhammad Ahmad; Dr. Abdus Salam; Dr. Mudassar Abdullah; Prof. Dr. Muhammad Ismail Kumbha; Sadia Munawar; Muhammad Hamid Nawaz Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the role of emotional intelligence (EI) in educational leadership, emphasizing its impact on leadership effectiveness within educational institutions. The research utilizes a quantitative approach to examine how EI influences leadership behaviors and outcomes. This study was correlational and descriptive in nature. This study was designed to find out relationship between emotional intelligence and educational leadership It was descriptive and quantitative in nature. Population of this research study was comprised of principal from different educational institutions from district Lahore. 75 institutes were selected from public sector educational institutions and 75 institutes were selected from private sector educational institution. In total 150 institutes were selected as population of the study. Principals of all these institutions were selected as sample of this current research study, so total 150 head of institutions. Three comprehensive adopted and standardized questionnaires were used as research instruments, with minor changes in the language, for data collection Different inferential statistics techniques were used to analyze data. As this study was correlational, comparative and quantitative in nature, Statistical techniques were used for data interpretation. Statistical Package for Social Sciences (SPSS) version 20.0 was used. Findings indicate a significant positive correlation between EI and leadership effectiveness. Specifically, leaders with higher EI scores tend to exhibit better self-awareness and self-management, which translate into improved decision-making and conflict resolution skills. Social awareness and relationship management are strongly linked to enhanced communication and team-building abilities, fostering a positive organizational climate. In conclusion, the study underscores the critical role of emotional intelligence in educational leadership, advocating for EI development programs as part of leadership training and professional development. Enhancing EI in educational leaders can lead to more effective leadership practices, ultimately benefiting the educational institution's overall performance and stakeholder satisfaction.